Effect of Zn addition on Cu3Sn formation in Sn-10Cu alloys. (December 2019) - Mehreen, Syeda U.; Nogita, Kazuhiro; McDonald, Stuart; StJohn, David
Abstract: Sn-Cu alloys have generated interest as potential candidates for high-temperature soldering applications, as they are economically feasible and environmentally safe. Sn-Cu alloys with copper contents beyond 7.6wt.% solidify with a primary Cu3 Sn phase, followed by peritectic and eutectic reactions. Typically, phases which form as elongated needles are undesirable, as they tend to be more brittle and in turn reduce the strength and toughness of the alloy. The effect of Zn on the peritectic reaction and phase formation in a Sn-10wt.%Cu alloy is investigated through cooling curves and microstructural analysis using optical and electron microscopy. Zn was alloyed in the range of 0.1-1wt.% to the base Sn-10Cu alloy system. The results indicate that the amount of the primary Cu3 Sn phase that forms is inversely proportional to the concentration of Zn. Although complete suppression of Cu3 Sn was not observed, there was a clear effect of Zn reducing the amount of the primary Cu3 Sn phase, with the greatest reduction of Cu3 Sn occurring with a 1wt.% Zn addition. The reduction of the elongated needle-shaped primary Cu3 Sn phase may find application in the development of more reliable bulk solder microstructures.